Литературный гуманизм - Силин, В.В. (Культура народов Причерноморья, 2013)
Новизна исследования состоит в доказательстве, что в истории литературы полностью
отсутствуют антигуманистические произведения, так как антигуманистическим идеям в
художественной литературе всегда противопоставляются подразумеваемые гуманистические идеи.
Этот вывод сделан на основании анализа положений некоторых теоретических работ, обзора
произведений разных художественных направлений и структурного анализа поэтики драмы Эжена
Ионеско «Лысая певица».
Ключевые слова: дегуманизация искусства, имманентность, диалогизм, театр абсурда. Новизна дослідження полягає у доказі, що в історії літератури антигуманістичних творів
зовсім не існує, тому що антигуманістичним ідеям в художньої літературі завжди протистоять
гуманістичні ідеї, що маються на увазі. Цей висновок було зроблено на підставі аналізу положень деяких
теоретичних робіт, огляду творів різних художніх напрямків, та структурного аналізу поетики драми
Ежена Іонеско «Лиса співачка».
Ключові слова: дегуманізація мистецтва, іманентність, діалогізм, театр абсурду. New idea of the research consists of proving that in the history of literature non-humanistic works
don’t exist at all because in the belles-lettres implied humanistic ideas are always opposed to non-humanistic
ones. This conclusion is made on the grounds of analysis of some theoretical articles (“Dehumanization of art”
by Ortega-y-Gasset, “Ortega end novel” by Goytisolo, “Foreign literature and literary critics” by Kozlov),
review of works of different artistic tendencies (classical tragedy, sentimentalism, romanticism, realism) and
structural analysis of poetics of the drama “La cantatrice chauve” (1950) by Eugene Ionesco.
The characters of this drama, Mr and Mrs Smith and Mr and Mrs Martin, are outwardly respectable English
ladies and gentlemen, but their respectabilité is absurd because they are all egoistic and don’t hear each other
while speaking. Their discussion is meaningless because it consists mostly of pauses and empty phrases about
someone who ties his laces, about another that reads a news-paper and so on. The deeds of the other characters,
housemaid and fireman, are also meaningless despite their activity.
At the end of the drama the author suggests to re-play its beginning under condition that characters change their
roles. The symbolic meaning of this cycle presents the non-humanistic idea of the drama as universal and fatal.
But an implied humanistic idea is opposed to, because the cycle admits the possibility to leave it at one of its
convolutions. This dialogical opposition of ideas is not resolved in the drama and presents an alternative to
spectators: should they submit the absurd, but habitual life they live or should they try to overcome it. So, the
drama by Eugene Ionesco illustrates very good the immanency of literary humanism by its dialogical conflict of non-humanistic and immanent humanistic ideas. Only the monological approach can present this drama as nonhumanistic.
Key words: dehumanization of arts, immanency, dialogism, theater of absurd.